PROTOTIPE SISTEM MONITORING DAN PENGGANTIAN OTOMATIS INTRAVENOUS FLUID DROPS - Afrizal Awlan Suryandaru; Nyoman Putra Sastra; Gst A Komang Diafari Djuni (Program Studi Teknik Elektro UNUD, 2021)
The giving of intravenous fluids to patients is dispense fluids into the veins using aninfusion set with a certain amount and period. Patients who are given intravenous fluids willconstantly be monitored by a nurse manually and regularly. In this study, a monitoring systemand automatic replacement of intravenous fluids drops were designed to make it easier fornurses to monitor and change infusions automatically. The monitoring system is designed totake advantage of the Telegram communication application integrated with the NodeMCUESP8266. In contrast, the automatic replacement system utilizes an infrared sensor to detectfluid availability. Based on the research results, the infrared sensor will have a logic '1' if infusionfluid is more than 50ml, and the sensor will have a logic '0' if infusion fluid is less than 50ml. Thefastest system response to send sensor data to Telegram Bot reached 01.10 seconds, while thefastest system response to receive orders from Telegram Bot reached 05.70 seconds.